Ali Shari’ati’s revolutionary Islamic thought and its relevance to the contemporary socio-political transformation - Anjar Nugroho; Tulus Warsito Surwandano (IAIN Salatiga, 2017)
Ali Shari’ati emerged as an enlightened intellectual figure in the phenomenonof the authoritarian and oppressive power of the Syah Pahlavi regime. Shari’atiappeared as a pioneer of radical ideas about Islam and the revolution whichstemmed from the Shi’a teachings that had been grafted into the revolutionary tradition of the Third World and Marxism. Shari’ati succeeded in establishing a revolutionary Islamic ideology that became the basis of the mass collective consciousness against the regime of the Syah. In Shari’ati’s thought, Islam is an emancipatory ideology and liberation. The progressive and revolutionary view of Shari’ati’s Islam derives from a belief system of tauhid. While tauhid in Shari’ati’s view is the unity among God, man and the universe, the society which is full of social discrimination, injustice, and arbitrariness can be categorized as Shirk, the opponent of tauhid. In the context of the Iranian revolution, the Shari’ati’s Islamic thought and ideology became the fourth t-text-stroke-width: 0px;